Macronutrient metabolism of adipose tissue at rest and during exercise: a methodological viewpoint - Frayn, K (1999)
The metabolism of white adipose tissue is regulated by many factors, including hormones and substrates delivered in the blood, the activity of the autonomic nervous system and the rate of flow of blood through the tissue. An integrated view of adipose tissue metabolism can only be gained, therefore, from studies in vivo. Of the various techniques available for studying adipose tissue metabolism in vivo, the measurement of arterio-venous differences offers some unique possibilities. In human subjects this technique has been performed mostly by catheterization of the venous drainage of the subcutaneous abdominal depot. Studies using this technique indicate that adipose tissue has an active pattern of metabolism, responding rapidly to meal ingestion by suppressing the release of non-esterified fatty acids, or to exercise with an increase in fat mobilization. Adipose tissue blood flow may also change rapidly in these situations; for instance, it increases markedly after a meal, potentially increasing the delivery of triacylglycerol to the enzyme lipoprotein lipase (EC 3.1.1.34) for hydrolysis. During exercise, there is evidence that adipose tissue blood flow does not increase sufficiently to allow delivery of all the fatty acids released into the systemic circulation. The various adipose tissue depots have their own characteristic metabolic properties, although in human subjects these are difficult to study with the arterio-venous difference technique. A combination of tracer infusion with selective catheterization allows measurements of leg, splanchnic and non-splanchnic upper-body fat mobilization and triacylglycerol clearance. Development of such techniques may open up new possibilities in the future for obtaining an integrated picture of adipose tissue function and its depot-specific variations.